Superação da profundidade de semeadura e densidades de palha para Mucuna aterrima, Mucuna deeringiana e Mucuna cinerea - Silva, G.b.f.; Azania, C.a.m.; Novo, M.c.s.s.; Wutke, E.b.; Zera, F.s. [UNESP]; Azania, A.a.p.m. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2013)
The experiment was conducted in a greenhouse to verify the ability of Mucuna aterrima, Mucuna cinerea and Mucuna deeringiana seeds to overcome different soil depths plus sugarcane straw densities. The experimental design was completely randomized with the treatments arranged in a factorial scheme 3 x 3 x 3 and four replications. The factors consisted of straw layers (0, 5, and 10 cm), Mucuna species (M. aterrima, M. cinerea and M. deeringiana) and sowing depth (1, 4 and 8 cm). The Mucuna species exceeded the sowing depth by 23 t ha‑1 straw and up to 8 cm, exposing the shoot to the surface from 10 days after emergence and also being able to develop height (> 96 cm per plant), leaf area (> 723 cm-2 per plant) and dry mass accumulation (> 2.09 g per plant) up to 35 DAS.

O experimento foi desenvolvido em casa de vegetação, com o objetivo de verificar a capacidade das sementes de Mucuna aterrima, Mucuna cinerea e Mucuna deeringiana para superar diferentes profundidades do solo acrescido de densidades de palha de cana-de-açúcar. O delineamento utilizado foi o inteiramente casualizado; os tratamentos foram distribuídos em esquema fatorial 3 x 3 x 3, com quatro repetições. Os fatores foram constituídos por camada de palha (0, 5 e 10 cm), espécies de Mucuna (M. aterrima, M. cinerea e M. deeringiana) e profundidade de semeadura (1, 4 e 8 cm). As espécies de Mucuna superaram até 23 t ha-1 de palha (10 cm) e até 8 cm de profundidade de semeadura, expondo as partes aéreas à superfície a partir dos 10 dias após emergência (DAS); elas foram capazes também de desenvolver a altura (>96 cm por planta), a área foliar (>723 cm-2 por planta) e o acúmulo de massa seca (>2,09 g por planta) até os 35 DAS.
Overcoming depth sowing and mulch density in Mucuna aterrima, Mucuna deeringiana and Mucuna cinerea
Keywords: sugarcane; straw; weed; cana-de-açúcar; palha; planta daninha